Steel plate shear walls having door openings with different arrangements of stiffeners. Issue 10 (July 2019) - Rostami, Parisa; Mofid, Massood
As steel plate shear walls are typically used in the building central cores around the elevators and stairs, introduction of an opening as door seems to be inevitable in steel plate shear wall spans. Due to the weakening of the steel plate shear walls' performance caused by this particular type of opening, the use of stiffeners around the opening is necessary. Nevertheless, introduction of stiffeners around all sides of the opening, which does continue to boundary elements, is very expensive and inefficient. Therefore, the study on the effect of different arrangements of stiffeners on the behavior of steel plate shear walls is significant. In this research, a number of steel plate shear walls with different characteristics in terms of the plate aspect ratio, location of openings, arrangement of stiffeners around the openings, and number of stories are designed, and also a series of nonlinear static analyses are performed. Then, the optimum locations of openings along with the arrangement of stiffeners for each case are identified based on the structural and economic criteria. Finally, a modified model, which is more efficient in terms of cost and performance in comparison with the similar unmodified model, is proposed.